급성폐쇄각발작의 과거력을 가진 백내장수술 시 수정체낭내확장고리의 효과 - 박정원; Jung Won Park; 정현호; Hyun Ho Jung; 박상우; Sang Woo Park (Daihan angwa haghoi jabji, 2013)
목적: 급성폐쇄각발작의 과거력을 가진 환자에서 백내장수술 중 수정체낭내확장고리(CTR) 삽입이 술 후 굴절력 및 전방깊이 및 부피에 어떠한 영향을 미치는지에 대해 알아보고자 하였다. 대상과 방법: 후향적으로 의무기록지를 조사하여 급성폐쇄각발작의 과거력을 가진 환자들 중 백내장수술을 받고 12개월 이상 경과 관찰이 가능하였던 45명 45안을 대상으로 하였으며, 수술 중 CTR를 사용한 군(n=21)과 사용하지 않은 군(n=24)으로 나누어, 술 후 1주일, 1, 3, 6, 12개월에 얻은 구면렌즈대응치(SE)와 술 전 예측 굴절력과의 차이를 비교 분석하였으며, 전방깊이 및 부피를 조사하였다. 결과: CTR를 사용한 군에서 술 후 SE와 예측굴절력의 차이는 6개월과 12개월시에 -0.59 ± 1.08D, -0.61 ± 1.04D였으며, 사용하지 않은 군에서는 -0.64 ± 1.30D, -0.67 ± 1.19D로 두 군간의 유의한 차이는 보이지 않았고(p=0.89, p=0.84), 두 군 모두에서 근시로 이행하는 경향을 보였다(p＜0.01). 술 후 전방깊이나 전방부피를 비교하였을 때에도, 두 군간의 차이는 없었다(p=0.13, p=0.47). 결론: 급성폐쇄각발작의 과거력을 가진 백내장수술 시 CTR 삽입은 CTR을 삽입하지 않을 경우에 비해 술 후 전방깊이 및 부피의 증가에 있어 유의한 차이가 없었으며, 술 후 근시화에도 유의한 차이를 보이지 않았다. <대한안과학회지 2013;54(9):1395-1400> Purpose: To evaluate the effect of a capsular tension ring (CTR) on the change in postoperative refractive errors and anterior chamber depth after cataract surgery in patients with a history of acute primary angle closure (APAC). Methods: We retrospectively reviewed medical records of 45 patients who underwent cataract surgery with a history of APAC. Forty five eyes were divided into 2 groups based on whether a CTR was implanted (n = 21) or not (n = 24). Spherical equivalent (SE) refractive errors were compared between the 2 groups for 12 months postoperatively. The postoperative anterior chamber depth (ACD) and volume (ACV) were compared between the 2 groups. Results: SE refractive errors in the CTR group were -0.59 ± 1.08 D at 6 months and -0.61 ± 1.04 D at 12 months postoperatively. In the non-CTR group, -0.64 ± 1.30 D, at 6 months and -0.67 ± 1.19 D at 12 months postoperatively. There was no statistically significant difference between 2 groups (p = 0.89, p = 0.84) and postoperative SE refraction shifted to myopic refractive power in both groups (p < 0.01). The postoperative ACD and ACV also showed no difference between the 2 groups (p = 0.13, p = 0.47). Conclusions: The postoperative ACD, ACV and myopic shift in patients with a history of APAC demonstrated no significant difference between CTR-implanted and non-CTR-implanted patient groups. J Korean Ophthalmol Soc 2013;54(9):1395-1400